Analysis of pathogenesis and drug treatment of chronic obstructive pulmonary disease complicated with cardiovascular disease - Li, Xiao-Fang; Wan, Cheng-Quan; Mao, Yi-Min (Frontiers in Medicine, 2022)
Chronic obstructive pulmonary disease (COPD) is a disease characterized by persistent airflow limitation, and is associated with abnormal inflammatory responses in the lungs to cigarette smoke and toxic and harmful gases. Due to the existence of common risk factors, COPD is prone to multiple complications, among which cardiovascular disease (CVD) is the most common. It is currently established that cardiovascular comorbidities increase the risk of exacerbations and mortality from COPD. COPD is also an independent risk factor for CVD, and its specific mechanism is still unclear, which may be related to chronic systemic inflammation, oxidative stress, and vascular dysfunction. There is evidence that chronic inflammation of the airways can lead to destruction of the lung parenchyma and decreased lung function. Inflammatory cells in the airways also generate reactive oxygen species in the lungs, and reactive oxygen species further promote lung inflammation through signal transduction and other pathways. Inflammatory mediators circulate from the lungs to the whole body, causing intravascular dysfunction, promoting the formation and rupture of atherosclerotic plaques, and ultimately leading to the occurrence and development of CVD. This article reviews the pathophysiological mechanisms of COPD complicated by CVD and the effects of common cardiovascular drugs on COPD.